Role of substrate on interaction of water molecules with graphene oxide and reduced graphene oxide. (October 2017) - Strzelczyk, Roman; Giusca, Cristina E.; Perrozzi, Francesco; Fioravanti, Giulia; Ottaviano, Luca; Kazakova, Olga
Abstract: We study local electronic properties of graphene oxide (GO) and reduced graphene oxide (RGO) on metallic (Pt) and insulating (Si3 N4 ) substrates in controlled humidity environment. We demonstrate that the supporting substrate plays a crucial role in interaction of these materials with water, with Pt making both GO and RGO insensitive to humidity variations and change in environment. On the other hand, in the case of Si3 N4 substrate a significant difference between GO and RGO with respect to humidity variations is demonstrated, indicating complete water coverage at ∼60% R.H for RGO and ∼30% R.H. for GO. Irrespective of the substrate, both GO and RGO demonstrate relative independence of their electronic properties on the material thickness, with similar trends observed for 1 and 2 layers when subject to humidity variations. This indicates a relatively minor role of material thickness in GO-based humidity sensors. Graphical abstract: